A framework for semantic model based on ontologies generation for e-government applications: case study of Tunisia Government. (2017) - Sta, Hatem Ben
This paper presents a framework for generating semantic model ontologies in OWL syntax from a government service domain. Firstly, the government service domain is analysed and domain ontology is constructed to capture its semantic content. Thereafter, a semiformal representation of the domain ontology is created with the ontology knowledge-based editor Protégé. Finally, the OWL ontology model is imported. This study aims at providing e-government developers, particularly those from the developing world, with an easy-to-use framework for practising semantic knowledge representation in e-government processes, thus facilitating the design of e-government systems that can be easily integrated and maintained. The other challenge when integrating information systems in any domain such as e-government is the challenge of interoperability. One can distinguish between three levels of interoperability: technical, semantic, and organisational. The technical aspect has been widely tackled especially after the ubiquity of internet technologies.